The Impacts of Refugees on Neighboring Countries : A Development Challenge - World Bank (Washington, DC, 2012)
Looks at the 42.3 million people,at the end of 2009, displaced globally as a result of conflict, violence, and human rights violations, of which, 27.1 million were internally displaced persons (IDPs) while 15.2 million were refugees outside their country of nationality or country of habitual residence, often living in protracted displacement situations in a host country. The largest percentage of refugees is found in countries neighboring their country of origin, most of which are middle-income countries;however, in some of these middle-income host countries, refugees dwell in low-income and fragile border regions. The impacts of refugees on the host country are not invariably negative, since refugees can make positive economic and social contributions to the host society and create opportunities for both the displaced and their hosts. Examples of initiatives for mitigating negative aspects and increasing positive impacts of refugees in host countries include International Conference on Central American Refugees (CIREFCA), The Zambia Initiative (ZI), and naturalization and local settlement of Burundian refugees in Tanzania.